A Geant4 Fano test for novel very high energy electron beams. (22nd December 2021) - McManus, M; Romano, F; Royle, G; Palmans, H; Subiel, A
Abstract: Objective. The boundary crossing algorithm available in Geant4 10.07-p01 general purpose Monte Carlo code has been investigated for a 12 and 200 MeV electron source by the application of a Fano cavity test. Approach. Fano conditions were enforced through all simulations whilst varying individual charged particle transport parameters which control particle step size, ionisation and single scattering. Main Results. At 12 MeV, Geant4 was found to return excellent dose consistency within 0.1% even with the default parameter configurations. The 200 MeV case, however, showed significant consistency issues when default physics parameters were employed with deviations from unity of more than 6%. The effect of the inclusion of nuclear interactions was also investigated for the 200 MeV beam and was found to return good consistency for a number of parameter configurations. Significance. The Fano test is a necessary investigation to ensure the consistency of charged particle transport available in Geant4 before detailed detector simulations can be conducted.